Strength Training in Children: A Systematic Review Study - Borys Bismark León-Reyes; Dilan Galeano-Rojas; Manuel Gámez-Vílchez; Claudio Farias-Valenzuela; Claudio Hinojosa-Torres; Pedro Valdivia-Moral (Children)
Background: With the increasing prevalence of sedentary lifestyles and childhood obesity, physical activity and exercise have emerged as essential pillars of health promotion in childhood. In this context, schools play a fundamental role as key players in the implementation of interventions that promote healthy habits and a more physically active life. Objectives: The purpose of the present study was to conduct a systematic review of the benefits of strength training in primary school students. Methods: The review was carried out using the Web of Science and Scopus databases, following the guidelines of the PRISMA statement and a PICO strategy. The studies were selected according to different inclusion and exclusion criteria, resulting in 11 scientific articles published in English during the last 5 years (2020–2024). The methodological quality of the studies was assessed using the STROBE checklist. Results: The results suggest that strength training with elementary school students improves physical and motor performance variables, as well as cognitive, psychosocial and health variables. Likewise, it can be observed that plyometric strength-training methods and unilateral and combined programs with aerobic and motor skills training are highly effective and favor adherence to physical exercise. This also demonstrates the importance and necessity of developing motor coordination skills from an early age, since they represent a determining factor in strength training as the exercises become more specific and complex. Conclusions: In conclusion, implementing strength training programs in primary education confers several benefits at an integral level for the students and is crucial to improving the lifestyle and quality of life of students.